Model tests and simulation analyses on lateral deformation characteristics of PVD-improved ground - Qichang WU; Fang XU; Qishu ZHANG; Yangfa PENG; Xu HAN; Bo RUAN; Qi YANG (Shuiwen dizhi gongcheng dizhi)
To explore the lateral deformation characteristics of prefabricated vertical drains (PVD)-improved soft ground under different preloading loads and provide guidance for the design and construction of relevant structures in soft deposit regions, this study analyzed the lateral deformation characteristics of PVD-improved ground under surcharge preloading and combined vacuum and surcharge preloading using large-scale model tests. The influence of loading rate (LR), surcharge load (ps), and vacuum pressure magnitude (|pv|) on the lateral deformation of PVD-improved ground under combined preloading was systematically studied using finite element analyses. The results show that the preloading under combined vacuum and surcharge could match faster loading rates and larger surcharge loads compared to surcharge preloading alone. In the subsequent consolidation stage after reaching maximum surcharge load, there is aninsignificant increase in the outward lateral deformation of PVD-improved ground under combined preloading; in contrast, the maximum outward lateral deformation of the ground under surcharge preloading could still increase by 10%, and the lateral deformation of localization depths could increase by over 30%. The lateral deformation profile of PVD-improved ground under combined preloading overall moves outward with the increase of ps and LR, and the decrease of the |pv|; meanwhile the lateral deformation rate and the depth of the maximum outward lateral deformation (δom) increase. The outward lateral deformation of PVD-improved presents step growth patterns during the surcharge loading process, and the δom increases approximately linearly with the increase of ps, but increases nonlinearly with the increase of LR and the decrease of |pv|. With the same load change, the variation in |pv| has a more significant impact on the ground lateral deformation compared to the variation in ps. This study can provide basic information for the analysis and design of soft ground improvement under combined vacuum pressure and surcharge load.